"What about users?": Development and validation of the mobile information security awareness scale (MISAS). Issue 2 (2nd December 2020) - Erdoğdu, Fatih; Gökoğlu, Seyfullah; Kara, Mehmet
Abstract : Purpose: The current study aimed to develop and validate Mobile Information Security Awareness Scale (MISAS) based on the prototype model for measuring information security awareness and the relevant literature. Design/methodology/approach: The scale was developed and validated with the participation of 562 students from four universities. The construct validity of the scale was tested through exploratory factor analysis and confirmatory factor analysis. Findings: The reliability of the scale was tested through corrected item-total correlations and Cronbach alpha. The MISAS includes six factors and 17 items. The identified factors were labeled as backup, instant messaging and navigation, password protection, update, access permission and using others' devices. Research limitations/implications: The scale included only the human aspects of mobile information security. The technical aspects are not within the scope of this study. For this reason, future studies might develop and validate a different scale focusing on the technical aspects of mobile information security. Originality/value: The developed scale contributes to the literature on the human aspects of mobile information security.